First Identification and Description of Rickettsioses and Q Fever as Causes of Acute Febrile Illness in Nicaragua. - Megan E Reller; Ijeuru Chikeka; Jeremy J Miles; J Stephen Dumler; Christopher W Woods; Orlando Mayorga; Armando J Matute (Public Library of Science (PLoS), 2016)
BACKGROUND:Rickettsial infections and Q fever present similarly to other acute febrile illnesses, but are infrequently diagnosed because of limited diagnostic tools. Despite sporadic reports, rickettsial infections and Q fever have not been prospectively studied in Central America. METHODOLOGY/PRINCIPAL FINDINGS:We enrolled consecutive patients presenting with undifferentiated fever in western Nicaragua and collected epidemiologic and clinical data and acute and convalescent sera. We used ELISA for screening and paired sera to confirm acute (≥4-fold rise in titer) spotted fever and typhus group rickettsial infections and Q fever as well as past (stable titer) infections. Characteristics associated with both acute and past infection were assessed. CONCLUSIONS/SIGNIFICANCE:We enrolled 825 patients and identified acute rickettsial infections and acute Q fever in 0.9% and 1.3%, respectively. Clinical features were non-specific and neither rickettsial infections nor Q fever were considered or treated. Further study is warranted to define the burden of these infections in Central America.